(3TQM ebOeg GdMOGFbs - (3GdCYQLj, GdMSjfj, GdcGXej, eMSf Hf MSf Hf GdeQJVi, J(B1227(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B...(3de jRd GdYdeGA(B...(3jJYdbhf HGdcJGH GdeLjO ceG jJYdbhf HGdSfI Hd jQOhfgG Edjg h jYQVhfgG Ydjg(B...s
(3BNQgG (B:s
(3LeghQ GdCUhdjjf ef CUMGHfG hZjQge Ydi MLjI bjGS GdChdhjI hefUhU GdYdI, Edi gfG cJH(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B:(3L(B5(3,U(B286s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B19s
(3GdPQjYI(B:(3L(B14(3,U(B53(3,JMJ Qbe (B1837s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis